In defense of a feeling account of pleasure - De Lazari-Radek, Katarzyna (Hybris, 2018)
Gilbert Ryle and Fred Feldman regard pleasure as, respectively, a disposition anda propositional attitude. I consider whether their accounts can seriously threaten the traditional understanding of pleasure in terms of feeling or sensation. I argue that their reluctance to treat pleasure as a mental state results from misunderstanding the difference between sensation and feeling. These concepts relate to different psychological phenomena and should not be used interchangeably. Understanding the difference between them makes it possible to defend the concept of pleasure in terms of feeling, though not sensation.